Hubungan Persepsi Dukungan Organisasi dengan Komitmen terhadap Organisasi Pada Pelaut di PT.X - Ni Made Senny Dwi Septyani; Sukmarani Sukmarani (MANASA, 2022)
The purpose of this study was to determine correlation between perceived organizational support with each dimension of organizational commitment, namely affective commitment, continuance commitment, and normative commitment to seafarers at PT.X. The hypothesis of this study is that there is a positive correlation between perceived organizational support and the affective commitment, continuance commitment and normative commitment to seafarers at PT.X. The method used in this research is correlational quantitative method. The subjects in this study were sailors at PT X with 47 participants. The technique of collecting participant data used is the proportionate stratified random sampling. The research instrument used the Survey Perceived Organizational Support (SPOS) scale and the Organizational Commitment Questionnaire (OCQ). The results of the Spearman's Correlation Coefficient correlation test show that there is no positive and significant correlation between perceived organizational support with affective commitment and continuance commitment, and there is a positive and significant correlation between perceived organizational support and normative commitment. The implication of this research is that companies can pay attention to and increase organizational support socially and emotionally in order to bring up the affective commitment, continuance commitment and normative commitment to seafarers in the company